CNF / NR dual cross-linked network-based heat conduction and storage material as well as preparation method and application thereof
By using the combination of CNF/NR dual crosslinking network and thermal filler in flexible phase change materials, the problem of poor dispersion effect and low thermal conductivity in the preparation process is solved, and high thermal conductivity and excellent protection are achieved Thermal thermal storage material for leakage performance.
Patent Information
- Application Number
- CN202411673740.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing flexible phase change materials have poor dispersion effect during the preparation process, including liquid phase leakage, high rigidity and low thermal conductivity.
Using thermally conductive heat storage material based on CNF/NR dual crosslinking network, the thermally conductive filler is dispersed into the CNF water suspension and mixed with phase change capsules to form a dense dual network structure, which improves the Thermal conductivity and leakage resistance.
It realizes efficient dispersion of thermally conductive heat storage materials, significantly improves the thermal conductivity coefficient to reach 1.023W/m·K, and has excellent leakage resistance, cycle stability and thermal stability.
Smart Images

Figure CN119505556A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phase change heat storage materials, and specifically relates to a heat conductive heat storage material based on a CNF / NR double cross-linked network, and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have become the main choice for electric vehicle energy storage systems due to their excellent performance such as high energy density, low self-discharge rate, long cycle life and environmental friendliness.
[0003] Among the PCM-based BTMSs reported to date, the most widely used PCMs are solid-liquid organic PCMs, particularly polyethylene glycol (PEG) and paraffin (or n-alkanes). Paraffin, in particular, has attracted considerable attention for its high latent heat, non-toxic and non-corrosive properties, excellent cyclic stability, and low cost and availability, making it widely used in BTMS. However, PCMs' inherent low thermal conductivity, insurmountable thermal expansion, leakage issues in the molten state, and a certain degree of supercooling have inevitably hindered their widespread practical application.
[0004] Combined with existing research, encapsulating phase change materials into microcapsules is considered to be an effective method. Phase change microcapsules (MPCMs) are spherical fillers with only a small area of overlap between fillers, making it difficult to form an interconnected thermal conductive network; therefore, the functional realization of phase change microcapsules usually requires the help of a carrier medium. Phase change microcapsules can be dispersed in a polymer cross-linked network to form a blended flexible composite phase change material with desired properties and functions. However, the inherent low thermal conductivity of organic MPCMs and polymers makes the prepared polymer-based flexible CPCM face the problem of low overall thermal conductivity, and due to the high specific surface area of MPCMs, it is easy to form serious aggregates in the polymer matrix. Nano-thermal conductive fillers are easy to agglomerate and deposit in the polymer matrix, and cannot establish effective interfacial contact; therefore, how to effectively regulate the distribution structure of thermal conductive fillers to improve the thermal conductivity while achieving good mechanical properties of flexible phase change materials is the key to obtaining high-performance flexible phase change materials. Summary of the Invention
[0005] The present invention aims to address, at least to some extent, one of the technical problems in the related art. To this end, the main purpose of the present invention is to provide a thermally conductive and heat storage material based on a CNF / NR dual cross-linked network and a method for preparing the material. This approach aims to address the problems of existing flexible phase change materials, such as poor dispersion during preparation, liquid phase leakage, high rigidity, and low thermal conductivity.
[0006] The present invention also provides the application of the heat-conducting and heat-storage material based on the CNF / NR double cross-linked network in photothermal materials and wearable materials.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network, the process flow is as follows Figure 1 As shown, the specific steps include:
[0009] 1) dispersing a certain amount of thermal conductive filler into a CNF aqueous suspension and homogenizing the mixture to obtain a first mixed solution;
[0010] 2) uniformly mixing the first mixed solution prepared in step 1) with the phase change capsules to obtain a second mixed solution;
[0011] 3) adding natural rubber latex dropwise into the second mixed solution prepared in step 2) and stirring uniformly to obtain a third mixed solution;
[0012] 4) The third mixed solution prepared in step 3) is frozen, dried and pressed to obtain a heat-conducting heat storage material.
[0013] In some specific embodiments, the thermal conductive material includes BNNS and MWCNT, and the mass ratio of BNNS to MWCNT is (3-8): (2-5).
[0014] Furthermore, the mass ratio of the BNNS to the MWCNT is 7:3.
[0015] In certain specific embodiments, the process parameters of the homogenization treatment in step 1) are homogenization at 4000-8000 rpm at room temperature for 5-15 min.
[0016] In certain specific embodiments, the freezing conditions in step 4) are freezing at -25 to -15°C for 6-18 hours; the drying conditions are freeze-drying at a pressure of less than 20 Pa and a temperature of -60 to -50°C for 40-50 hours; and the pressing conditions are pressing at room temperature and 1-3 MPa for 3-8 minutes.
[0017] In certain specific embodiments, the mass percentage of the thermally conductive filler in the thermally conductive heat storage material is 4-12%.
[0018] In certain specific embodiments, the natural rubber latex is NR natural rubber latex, the phase change capsules are phase change paraffin microcapsules, and the mass fraction of the CNF aqueous suspension is 1-3%.
[0019] Furthermore, the mass fraction of the CNF aqueous suspension is 1.3%.
[0020] In some specific embodiments, the mass ratio of the phase change capsules to CNF is (5-15):1.
[0021] Furthermore, the mass ratio of the phase change capsules to CNF is 10:1.
[0022] In certain specific embodiments, the mass ratio of the phase change capsules to NR is (4-8):(2-5).
[0023] Furthermore, the mass ratio of the phase change capsules to NR is 7:3.
[0024] A heat-conducting and heat-storage material prepared by the aforementioned preparation method.
[0025] An application of the aforementioned heat-conducting and heat-storage material in photothermal materials and wearable materials.
[0026] 1) This application uses cellulose nanofibers (CNF) as a dispersant to effectively disperse phase-change paraffin microcapsules (MPCM) in a natural rubber (NR) matrix. The NR cross-linked network and the CNF cross-linked network are interwoven, and the CNF network directly penetrates the NR matrix, promoting the dispersion of the MPCM while making the dual network structure more dense, supplementing the significant anti-leakage performance of the thermal conductive and thermal storage material.
[0027] 2) The thermal conductive heat storage material of the present application is only physically mixed and evenly dispersed during the entire preparation process. CPCM is prepared by mixing and pressing at room temperature. The process is simple and efficient, without harsh experimental conditions such as high temperature and high pressure, and is suitable for large-scale production applications.
[0028] (3) The CNF / BNNS / MWCNT network formed by the self-assembly strategy of the present invention plays the role of constructing a connected thermal conductive network; when the added content of BNNS / MWCNT is 12wt%, a perfectly connected thermal conductive network is constructed, enabling rapid heat transfer, and the thermal conductivity reaches 1.023W / m·K, which is 499% of the thermal conductivity of NC@M, while maintaining a high phase change latent heat value of 110.04J / g.
[0029] (4) Based on the triple synergistic encapsulation effect of the core-shell structure of paraffin phase change microcapsules, the cross-linked network of NR unsaturated bonds, and the cross-linked network of CNF hydrogen bonds, the flexible NCBM@M thermal conductive and heat storage material obtained in the present invention exhibits excellent complete leakage-proof performance, as well as excellent cyclic stability and thermal stability, showing great potential in practical applications.
[0030] (5) The continuous NR flexible cross-linked network in the present invention endows the thermal conductive and thermal storage material with excellent room-temperature flexibility and stretchability. NCBM@M can be bent, stretched, and twisted at room temperature, with a wide flexibility temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific embodiments of the present invention, the following briefly introduces the drawings required for the specific embodiments or the description of the prior art.
[0032] Figure 1 This is a flow chart for preparing the heat-conducting and heat-storage materials provided in the present invention;
[0033] Figure 2 FT-IR images (a) and XED test images (b) of MPCM, NC@M and NCBM@M in the present invention;
[0034] Figure 3 SEM images of MPCM and NC@M, NCBM4@M, NCBM8@M and NCBM12@M in the present invention;
[0035] Figure 4 Graph showing thermal conductivity of NC@M, NCBM4@M, NCBM8@M, and NCBM12@M in Examples 1-4 of the present invention;
[0036] Figure 5 (a) and (b) DSC curves of the heating process of MPCM and NC@M, NCBM4@M, NCBM8@M and NCBM12@M in the present invention;
[0037] Figure 6 Flexibility test images of NC@M, NCBM4@M, NCBM8@M, and NCBM12@M in Examples 1-4 of the present invention; (a) digital image of NCBM12@M; (b-c) digital images of NCBM12@M during bending and twisting; (d) stress-strain curve of the sample; (e) tensile strength and elongation at break of the sample; (f) digital image of NCBM12@M pulling a 500g weight;
[0038] Figure 7 Digital images of NCBM4@M, NCBM8@M, and NCBM12@M in Examples 2-4 of the present invention at 80°C and 500g pressure, as well as digital images after continuous heating at 80°C for 120h;
[0039] Figure 8 are the phase transition temperature and phase transition enthalpy of NCBM12@M in Example 4 of the present invention before and after 100 heating and cooling cycles;
[0040] Figure 9 (a) TGA curves and (b) DTG curves of MPCM, NC@M and NCBM12@M in the present invention;
[0041] Figure 10Thermal management test diagram of NC@M, NCBM3.6@M and NCBM12@M in the present invention;
[0042] Figure 11 The temperature distribution diagram of the surface of NC@M and NCBM12@M materials in the present invention changes with time. DETAILED DESCRIPTION
[0043] The present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are merely illustrative and non-restrictive, and should not be used to limit the scope of protection of the present invention.
[0044] When expressing a certain amount, concentration or other value or parameter in the form of a range, preferred range, or preferred upper and lower numerical limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, without considering whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range and all integers and fractions within the range.
[0045] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0046] The materials, methods, and examples herein are illustrative and, unless otherwise indicated, are not to be construed as limiting.
[0047] In the following examples, the thermal conductive material used is a mixture of multi-walled carbon nanotubes (MWCNTs) and boron nitride nanosheets (BNNS); the phase change capsules used are phase change paraffin microcapsules; and the natural rubber latex used is NR natural rubber latex. The main raw materials and technical specifications used are shown in Table 1:
[0048] Table 1 Experimental materials and specifications
[0049]
[0050] Physical characterization and performance testing of the materials used in the following examples:
[0051] 1) The surface morphology and microstructure of the materials were analyzed and tested using a scanning electron microscope (SEM). Before testing, the samples were surface-sprayed with gold to improve the conductivity of the materials and enhance imaging clarity. SEM images were captured using a Quattro S (Thermo Fisher Scientific) at an accelerating voltage of 5–20 kV.
[0052] 2) The chemical structure of the materials was analyzed by Fourier transform infrared spectroscopy (FT-IR). FT-IR spectra were obtained by a Nicolet iS50 infrared spectrometer (Thermo Fisher Scientific) at room temperature in the range of 4000–400 cm -1 , with a resolution of 4cm -1 .
[0053] 3) The crystal structure of the material was characterized and analyzed by X-ray diffraction (XRD); the XRD pattern was obtained by Empyrean (PANalytical, the Netherlands) with a voltage of 40 kV, a current of 40 mA, a scanning range of 5°-80°, and a scanning speed of 5° / min.
[0054] 4) The thermal conductivity of the PCM sample was directly measured using a thermal constant analyzer (Hot Disk TPS2500S) based on the transient plane heat source method. The test temperature was 25°C, the test number was 3, and the average value was taken as the final result.
[0055] 5) The phase change characteristics of the PCM samples were studied using a differential scanning calorimeter (DSC) to determine thermal performance parameters such as phase transition temperature and latent heat of phase change. Under a nitrogen purge (50 ml / min), the temperature was raised / lowered at a rate of 5°C / min over a scanning range of 20–60°C.
[0056] 6) The cyclic stability of the sample is determined by thermal cycling testing to ensure that its phase change characteristics do not change during long-term operation; specifically, the stability is ensured by characterizing the DSC curves of the sample before and after the thermal cycling test.
[0057] 7) Dynamic Thermomechanical Analysis (DMA) is used to test the flexibility properties of the samples.
[0058] 8) The thermal stability of the material was investigated using a thermogravimetric analyzer (TGA). The sample mass was 3-5 mg, and the test was performed in a nitrogen atmosphere (50 ml / min) over a temperature range of 30°C to 600°C at a heating rate of 10°C / min.
[0059] 9) To test the shape stability of the samples, the PCM series samples were placed in a constant temperature drying oven and heated continuously at 80°C for a period of time. They were then taken out and weighed again using an electronic balance to calculate the mass leakage rate of the samples. The formula for calculating the sample leakage rate after heating n times is shown in (2.5):
[0060]
[0061] Among them L n and M n They represent the leakage rate and remaining mass of the sample in the nth test respectively; M0 is the initial mass of the sample.
[0062] Example 1
[0063] This embodiment provides a method for preparing a thermal conductive and heat storage material based on a CNF / NR dual cross-linked network, which specifically includes the following steps:
[0064] 1) uniformly mixing a CNF aqueous suspension having a mass concentration of 1.3% with phase-change paraffin wax microcapsules (MPCM), wherein the mass ratio of the phase-change paraffin wax microcapsules to the CNFs is 10:1, to obtain a mixed solution A;
[0065] 2) adding NR natural rubber latex dropwise into the mixed solution A prepared in step 1), wherein the mass ratio of phase change paraffin microcapsules (MPCM) to NR natural rubber latex in the mixed solution A is 7:3, and stirring uniformly to obtain a third mixed solution;
[0066] 3) The third mixed solution prepared in step 2) was frozen at -20°C for 12 hours, and then immediately transferred to a freeze dryer for freeze drying for 48 hours (-55°C, <20 Pa). The resulting solid material was pressed at room temperature and 2 MPa for 5 minutes to eliminate internal air, thereby obtaining a thermal conductive heat storage material (abbreviated as NC@M).
[0067] Example 2
[0068] This embodiment provides a method for preparing a thermal conductive and heat storage material based on a CNF / NR dual cross-linked network, which specifically includes the following steps:
[0069] 1) dispersing a thermal conductive filler of BNNS and MWCNT in a mass ratio of 7:3 (the thermal conductive filler accounts for 4% in the thermal conductive heat storage material) into a CNF aqueous suspension with a mass concentration of 1.3%, and homogenizing to obtain a first mixed solution;
[0070] 2) uniformly mixing the first mixed solution prepared in step 1) with phase change paraffin microcapsules (MPCM), wherein the mass ratio of the phase change paraffin microcapsules (MPCM) to the CNFs in the first mixed solution is 10:1, to obtain a second mixed solution;
[0071] 3) adding NR natural rubber latex dropwise into the second mixed solution prepared in step 2), wherein the mass ratio of phase change paraffin microcapsules (MPCM) to NR natural rubber latex in the second mixed solution is 7:3, and stirring uniformly to obtain a third mixed solution;
[0072] 4) The third mixed solution prepared in step 3) was frozen at -20°C for 12 h, and then immediately transferred to a freeze dryer for freeze drying for 48 h (-55°C, <20 Pa). The resulting solid material was pressed at room temperature and 2 MPa for 5 min to eliminate internal air, thereby obtaining a thermal conductive heat storage material (abbreviated as NCBM4@M).
[0073] Example 3
[0074] This embodiment provides a method for preparing a thermal conductive and heat storage material based on a CNF / NR dual cross-linked network, which specifically includes the following steps:
[0075] 1) dispersing a thermally conductive filler of BNNS and MWCNT in a mass ratio of 7:3 (the thermally conductive filler accounts for 8% in the thermal conductive heat storage material) into a CNF aqueous suspension with a mass concentration of 1.3%, and homogenizing the suspension to obtain a first mixed solution;
[0076] 2) uniformly mixing the first mixed solution prepared in step 1) with phase change paraffin microcapsules (MPCM), wherein the mass ratio of the phase change paraffin microcapsules (MPCM) to the CNFs in the first mixed solution is 10:1, to obtain a second mixed solution;
[0077] 3) adding NR natural rubber latex dropwise into the second mixed solution prepared in step 2), wherein the mass ratio of phase change paraffin microcapsules (MPCM) to NR natural rubber latex in the second mixed solution is 7:3, and stirring uniformly to obtain a third mixed solution;
[0078] 4) The third mixed solution prepared in step 3) was frozen at -20°C for 12 h, and then immediately transferred to a freeze dryer for freeze drying for 48 h (-55°C, <20 Pa). The resulting solid material was pressed at room temperature and 2 MPa for 5 min to eliminate internal air, thereby obtaining a thermal conductive heat storage material (abbreviated as NCBM8@M).
[0079] Example 4
[0080] This embodiment provides a method for preparing a thermal conductive and heat storage material based on a CNF / NR dual cross-linked network, which specifically includes the following steps:
[0081] 1) dispersing a thermally conductive filler of BNNS and MWCNT in a mass ratio of 7:3 (the thermally conductive filler accounts for 12% in the thermal conductive heat storage material) into a CNF aqueous suspension with a mass concentration of 1.3%, and homogenizing the suspension to obtain a first mixed solution;
[0082] 2) uniformly mixing the first mixed solution prepared in step 1) with phase change paraffin microcapsules (MPCM), wherein the mass ratio of the phase change paraffin microcapsules (MPCM) to the CNFs in the first mixed solution is 10:1, to obtain a second mixed solution;
[0083] 3) adding NR natural rubber latex dropwise into the second mixed solution prepared in step 2), wherein the mass ratio of phase change paraffin microcapsules (MPCM) to NR natural rubber latex in the second mixed solution is 7:3, and stirring uniformly to obtain a third mixed solution;
[0084] 4) The third mixed solution prepared in step 3) was frozen at -20°C for 12 h, and then immediately transferred to a freeze dryer for freeze drying for 48 h (-55°C, <20 Pa). The resulting solid material was pressed at room temperature and 2 MPa for 5 min to eliminate internal air, thereby obtaining a thermal conductive heat storage material (abbreviated as NCBM12@M).
[0085] Performance testing:
[0086] The present application conducted performance tests on the thermal conductive and heat storage materials prepared in Examples 1-4, specifically:
[0087] (1) Chemical compatibility and crystallinity
[0088] This test example takes Example 1 and Example 2 as examples, and FT-IR characterization is performed on MPCM, NC@M (Example 1) and NCBM@M (Example 2). Figure 2 As shown in (a), it can be seen from the spectrum of MPCM that 2916 cm -1 and 2848cm -1 The absorption peaks at 1471 cm and 1472 cm are attributed to the stretching vibration of the CH bond in the -CH3 and -CH2 groups, which are typical characteristics of alkanes. The asymmetric stretching vibration and rocking vibration of -CH2 appear at 1471 cm -1 and 717cm -1 It is worth noting that compared with pure MPCM, NC@M and NCBM@M have the typical characteristic peaks of cellulose materials, 3335cm -1 The absorption peak at 891 cm- -1 The absorption peak at 842 cm corresponds to the glycosidic bond of cellulose; after adding NR, NC@M and NCBM@M -1The new absorption peak generated at 1310 cm corresponds to the in-plane rocking vibration of -CH2; the NCBM@M peak at 1310 cm -1 and 769cm -1 The two characteristic peaks appearing at 1660 cm correspond to the bending vibration of BNB and the stretching vibration of BN respectively; -1 The new absorption peak at corresponds to the C=C stretching vibration. Furthermore, the main absorption peaks of MPCM and NC@M are observed in the NCBM@M spectrum, indicating that MPCM successfully binds to the other components through physical interactions without generating new functional groups. The physical crosslinking, without chemical reaction, between MPCM, NR, CNF, BNNS, and MWCNTs demonstrates the good chemical compatibility of NCBM@M.
[0089] This test example also carried out XRD tests on MPCM, NC@M (Example 1) and NCBM@M (Example 2). The results are as follows: Figure 2 As shown in (b), the three characteristic diffraction peaks of MPCM are located at 19.4°, 23.4° and 24.9°, respectively, representing the (110), (200) and (210) crystal planes of the phase change paraffin microcapsules (MPCM). All diffraction peaks of MPCM and NC@M are observed in the diffraction pattern of the thermal conductive heat storage material NCBM@M. There is no obvious shift in the position of the diffraction peaks, only a slight decrease in intensity. Among them, the new diffraction peaks at 26.7°, 41.7°, 43.6°, 49.8°, 55.1° and 75.9° in the diffraction pattern of NCBM@M also correspond to the (002), (100), (101), (102), (004) and (110) crystal planes of BNNS, respectively. In summary, it is shown that during the entire synthesis process of the thermal conductive heat storage material, only physical mixing was carried out, and no chemical reaction occurred between the melting and mixing of any individual components.
[0090] (2) Microstructure and morphology
[0091] The present application conducts microstructure and morphology tests on the MPCM and the heat-conducting and heat-storage materials in Examples 1-4, and the SEM images thereof are shown in FIG. Figure 3 As shown, Figure 3 (a) is a SEM image of MPCM, showing microclusters formed by the mutual attraction of many MPCMs. This is because MPCMs are small in size, large in specific surface area, and high in surface energy, and they can easily self-assemble to form aggregates. If these MPCM aggregates are directly and randomly dispersed in the NR matrix, it is easy to form an island structure similar to polymer blending, which will introduce more interface defects to the NR matrix. Figure 3As shown in (b), the addition of CNF obviously improves the compatibility between MPCM and NR. CNF is wrapped in the form of a strip on the NR / MPCM composite material, and at the same time, the uniform dispersion of MPCM in the NR matrix is achieved. The cross-linked network derived from the unsaturated bonds of NR and the cross-linked network derived from the hydrogen bonding of CNF are intertwined with each other, and the three-dimensional continuous CNF network directly penetrates the NR matrix, making the encapsulation network denser. The double flexible network formed can give the thermal conductive heat storage material good flexibility. That is, the double encapsulation network formed by NR and CNF will also give the thermal conductive heat storage material excellent anti-leakage performance. As shown in Figure 3 As shown in (ce), with the introduction of BNNS / MWCNT binary thermal conductive fillers, the CNF skeleton becomes significantly thicker, indicating that BNNS / MWCNTs are successfully attached to the CNF skeleton, which is conducive to the construction of a highly interconnected and uniform thermal conductive network; with the increase of BNNS / MWCNT content on CNF, the CNF / BNNS / MWCNT network also becomes denser.
[0092] (3) Thermal conductivity
[0093] This test example tests the thermal conductivity of the heat storage materials prepared in Examples 1-4 at 25°C. The results are as follows: Figure 4 As shown in the figure, the thermal conductivity of NCBM@M increases with increasing BNNS / MWCNT binary thermally conductive filler content. SEM images show that the CNF cross-linked network directly penetrates the entire NR matrix, which facilitates the construction of highly connected thermal conductive pathways within the NR matrix. Therefore, when the BNNS / MWCNT content increases from 0wt% to 12wt%, the BNNS / MWCNTs fill and contact each other on the CNF cross-linked network, forming and improving the thermal conductive network. The thermal conductivity of NCBM4@M is 0.462 W / m·K, and the thermal conductivity of NCBM8@M is 0.727 W / m·K, which are 225% and 355% of the thermal conductivity of NCBM@M, respectively. The thermal conductivity of NCBM12@M reaches its maximum value of 1.023 W / m·K, which is 499% of the thermal conductivity of NC@M. This is mainly attributed to the fact that BNNS / MWCNT, at an addition amount of 12 wt%, constructs and improves a better thermal conductive network, enabling heat to be quickly transferred through the channels of the network, thereby greatly improving the thermal conductivity coefficient, that is, the thermal conductive heat storage material of the present application has excellent thermal conductivity.
[0094] (4) Phase change behavior and heat storage performance
[0095] In this test case, the phase change characteristics of MPCM and NCBM@M thermal conductive storage materials were measured by DSC to evaluate the heat storage capacity of the materials. Figure 5 The DSC curves of a series of samples are shown. Figure 5(a) Phase change characteristics of the MPCM and NCBM@M thermal conductive storage materials during heating. Figure 5 (b) shows the phase change characteristics of the MPCM and NCBM@M thermal conductivity and heat storage materials during the cooling process. Table 2 lists the melting temperatures (T m ), melting enthalpy (ΔH m ), crystallization temperature (T f ), crystallization enthalpy (ΔH f ) and subcooling (ΔT).
[0096] Table 2 Phase change temperature, phase change enthalpy and supercooling of MPCM and series NCBM@M thermal storage materials
[0097]
[0098] Combine Figure 5 From the data in Table 2, it can be seen that MPCM has higher melting enthalpy (188.64 J / g) and crystallization enthalpy (184.82 J / g), with melting and crystallization temperatures of 44.25°C and 32.84°C, respectively. During the crystallization process, the solidification point of the prepared NCBM@M thermal storage material was higher than that of MPCM. This is because the NCBM@M thermal storage material with a higher thermal conductivity has a faster heat transfer rate, absorbing or releasing more heat in the same duration, thereby accelerating the phase change. Therefore, its crystallization occurs earlier than that of pure MPCM, and the solidification point temperature is increased. The melting and crystallization temperatures of the NCBM12@M thermal storage material are 44.32°C and 38.14°C, respectively. Compared with pure MPCM, the supercooling of the NCBM12@M thermal storage material is reduced from 11.41°C to 6.18°C, which is beneficial for the utilization of phase change materials.
[0099] The sample was prepared by simple physical mixing without any chemical reaction, so the theoretical latent heat value ΔH of the sample should follow the following formula:
[0100] ΔH=ΔH MPCM ×α (4.1)
[0101] Where ΔH MPCMrepresents the latent heat of the MPCM, and α represents the mass fraction of the MPCM in the thermal conductive storage material. The results show that the latent heat of the NCBM@M thermal conductive storage material is not much different from the theoretical calculation results, indicating that the MPCM is uniformly distributed in the NCBM@M. Due to the incorporation of the non-phase change components NR, CNF, BNNS, and MWCNT, the latent heat of the prepared NCBM@M thermal conductive storage material is significantly lower than that of the MPCM. The melting enthalpy and crystallization enthalpy of the NCBM12@M thermal conductive storage material are 110.04 J / g and 107.56 J / g, respectively, which are 41.67% and 41.80% lower than those of the MPCM. The NCBM12@M thermal conductive storage material has a heat storage density of 110.04 J / g, which meets the requirements of battery thermal management.
[0102] (5) Flexible characteristics
[0103] This test example tests the flexibility and stretchability of the heat-conducting and heat-storage materials prepared in Examples 1-4. The results are as follows: Figure 6 As shown, from Figure 6 As can be seen from the actual photo of (a), the thickness of the NCBM@M thermal conductive and heat storage material is 1.2 mm, and the surface is smooth and flat. Figure 6 As shown in Figures 6(b) and 6(c), the prepared NCBM@M thermal conductive storage material can be easily bent and twisted at large angles, showing excellent room temperature flexibility. The tensile strength of the NCBM@M thermal conductive storage material is largely dependent on the NR loading.
[0104] NCBM@M sample (13×5×1.2mm 3 ) were tested by tensile model. The results show that the surface NCBM12@M sample still maintains good mechanical properties. According to the typical stress-strain curve of NCBM@M thermal conductive heat storage material, the tensile strength and elongation at break were obtained, as shown in 6(d) and 6(e). NCBM12@M thermal conductive heat storage material can withstand a stress of 2.55MPa, and the corresponding elongation can reach 11.12%, indicating that it has excellent flexibility. The enhancement of the mechanical properties of the thermal conductive heat storage material is attributed to the uniform dispersion of CNF / BNNS / MWCNT in the continuous NR network and fewer defects. As Figure 6 As shown in (f), a 0.2g NCBM12@M with a cross-sectional size of 5mm×1.5mm can lift a weight of 500g, intuitively demonstrating its high strength and good flexibility. This means that NCBM12@M thermal conductive and heat storage materials with excellent flexibility have considerable application potential in real life.
[0105] (6) Stability
[0106] (61) Shape stability
[0107] In this test example, the thermal conductive heat storage materials prepared in Examples 1-4 were placed on a constant temperature heating table and heated to 80°C to test the shape stability and anti-leakage performance of the NCBM@M thermal conductive heat storage materials. The results are as follows: Figure 7 As shown in the figure, when heated above the phase transition temperature, no obvious shape change or liquid leakage was observed for NCBM4@M, NCBM8@M, and NCBM12@M under the pressure of a 500g weight. To further quantify the leakage of PCM, the NCBM@M series samples were placed in a constant temperature drying oven at 80°C and heated continuously for 120 hours. It can be seen that after 120 hours, the surface of the glass dish remained dry and the thermal conductive heat storage material had almost no mass loss. Obviously, based on the triple encapsulation effect of the core-shell structure of the phase change paraffin microcapsules, the NR three-dimensional cross-linked network, and the CNF three-dimensional cross-linked network, the obtained flexible NCBM@M thermal conductive heat storage materials all exhibited excellent and completely leak-proof performance, showing great potential in practical applications.
[0108] (62) Cyclic stability and thermal stability
[0109] This test example tests the cyclic stability and thermal stability of the heat-conducting and heat-storage materials prepared in Examples 1-4. Figure 8 As shown, Figure 8 The DSC curves of the NCBM12@M thermal conductive storage material before and after 100 heating / cooling cycles are shown. The results show that compared to the first heating / cooling cycle of the NCBM12@M thermal conductive storage material, the phase transition temperature and enthalpy values after 100 cycles remain almost unchanged. The material maintains a high enthalpy (115.87 J / g) and a loss of less than 1%, demonstrating excellent cyclic stability. The chemical structure of the NCBM12@M thermal conductive storage material remains stable after 100 heating / cooling cycles.
[0110] In addition, the thermal stability of the heat-conducting and heat-storage materials prepared in Examples 1-4 was evaluated by thermogravimetric analysis (TGA). Figure 9 As shown, Figure 9(a) shows the TGA curves of MPCM, NC@M and NCBM12@M. As can be seen from the figure, the components of the materials remain stable within the range of 0 to 180°C; MPCM has low thermal stability and begins to thermally decompose at 180°C. The main mass loss occurs between 180 and 450°C, accompanied by three thermal decomposition stages; the mass loss of NC@M and NCBM12@M thermal conductive and heat storage materials occurs between 190 and 450°C, accompanied by two-step thermal decomposition. This shows that the thermal decomposition rate intensifies with increasing temperature. It is well known that BNNS and MWCNT have extremely stable chemical properties and will not undergo obvious thermal decomposition at temperatures as high as 800°C. The results show that the char residue of NCBM12@M is about 11.8%. This is basically consistent with the loading ratio of MWCNT and BNNS in the corresponding NCBM12@M composite material. In order to further reveal the thermal decomposition behavior of the phase change material, the derivative thermogravimetric (DTG) curve of the material was obtained based on the TGA data, as shown in the figure. Figure 9 (b) As shown. For thermal conductive heat storage materials, the first step on the TGA curve is the thermal decomposition process of MCPW. Compared with pure MPCM, the prepared NC@M and NCBM12@M thermal conductive heat storage materials both complete decomposition at higher temperatures. After 350°C, NR and CNF undergo rapid thermal decomposition due to the breakage of their molecular chains and the gradual decomposition of oligomers into low molecular weight compounds and volatilization. In summary, the weight loss rate of NCBM12@M is slower and the weight loss is completed at a higher temperature. It can be proved that the prepared NCBM12@M has better thermal stability than pure MPCM, which is very beneficial for its safe use in thermal management systems.
[0111] 7) Thermal management and resistivity testing
[0112] This test example takes Example 4 as an example, and uses the NCBM12@M module to control the temperature of the thermal conductive heat storage material prepared therefrom. The module uses a polyimide (PI) heating tape as a heat source inserted into the NCBM12@M. Figure 10 (a) Schematic diagram showing the experimental setup and heat storage / release process, including the arrangement of thermocouples.
[0113] Figure 10 (b) shows the time-dependent surface temperature evolution of the NCBM12@M module. The two test points exhibit consistent trends, indicating that the temperature is uniform throughout the entire heat storage and release cycle. During the discharge phase, the first phase transition results in the release of latent heat from point C to point D. Subsequently, after a partial release of sensible heat (point D to point E), the second phase of conversion to latent heat release (point E to point F) begins, maintaining the surface temperature between 30 and 31°C for 6 minutes. Point F represents the end of the entire phase transition. The results demonstrate the two-stage temperature control capability and high thermal efficiency potential of NCBM12@M. Figure 10(c) The effect of module thickness on the constant surface temperature of the two stages is further analyzed. The obtained results provide guidance for designing module specifications that meet practical requirements.
[0114] At the same time, this test example also tests the resistivity (ρ) of the thermal conductive and thermal storage materials NC@M, NCM3.6@M (NCBM12@M sample without BNNS, specifically its preparation method is the same as that of Example 4, except that BNNS is not added) and NCBM12@M. Figure 10 (d). The resistivities of NC@M sample, NCM3.6@M sample (NCBM12@M sample without BNNS) and NCBM12@M sample are approximately 2.47×1010Ω-m, 2.64×108Ω-m and 7.77×109Ω-m, respectively. These findings indicate that NR and MPCM have good insulating properties. After adding MWCNTs, the resistivity is significantly reduced, which is mainly due to the enhanced conductivity of MWCNTs. BNNS has a very high resistivity, and its addition significantly enhances the insulating properties of CPCM. This shows that BNNS and MWCNTs
[0115] They can be effectively dispersed in CPCM to form an interconnected network, thereby significantly suppressing the conductivity of CPCM.
[0116] The application of the thermal conductive heat storage material as a wearable material in this application is as follows: by reducing the peak surface operating temperature or excellent temperature control performance, we further apply the NCBM12@M module to the human arm ( Figure 10 (f) ) as an example of hyperthermia to evaluate its effectiveness in personal thermal management. The increased flexibility and bioavailability of the NR / CNF substrate allowed for the fabrication of large-scale NCBM12@M modules that can be bent to conform to the curvature of the human arm without leaking the NCBM12@M. For ethical reasons, a temperature-controlled module with a thickness of 3.5 mm was used to allow for testing of multiple heating-cooling cycles on human subjects. Figure 10 The heat charge-release curve in (e) shows that after the first charge, the optimal human body temperature range of 36-40°C can be maintained for more than 10 minutes. Furthermore, after the second and third short-term charges, the stagnation time associated with thermal comfort temperature is almost the same as that of the first charge. Infrared thermal images also show that the F-FSPCMs module can evenly release heat to the arm after charging, enabling the F-FSPCMs module to exhibit excellent thermal therapy effects and show improved thermal cycling stability and long-term service life in practical applications.
[0117] 8) Photothermal conversion performance test
[0118] This test example tests the light-to-heat conversion performance of the thermal conductive and heat storage materials prepared in Examples 1-4, specifically:
[0119] The photothermal conversion performance test system in this test example consists of a xenon lamp, an infrared camera, and a temperature collector ( Figure 11 Figure 2 (a). A PCM sample with a diameter of 2 cm and a height of 0.4 mm was subjected to a constant irradiation intensity of 100 mW / cm² through a solar simulator. Temperature fluctuations at the bottom of the PCM sample were recorded using a thermocouple and a temperature collector. The temperature distribution on the PCM sample surface over time was recorded using an infrared camera.
[0120] The temperature-time curve of the photothermal conversion experiment is as follows Figure 11 As shown in Figures 11(b) and 11(c), the temperatures of the PCM samples (NC@M and NCBM12@M) increased under simulated illumination conditions. After 25 minutes of irradiation, the temperature of NC@M reached only 37.3°C, significantly below its melting point (approximately 39°C). This indicates relatively poor photothermal conversion performance. In contrast, the temperature of the bottom layer of NCBM12@M increased rapidly with increasing illumination time. Furthermore, a phase transition process was clearly visible between 38°C and 40°C. The surface temperature distributions of NCBM12@M and NC@M exhibited similar patterns. Furthermore, it was observed that the surface temperature of NCBM12@M was higher than that measured by the thermocouple. This discrepancy is attributed to the placement of the thermocouple at the bottom of the NCBM12@M sample. When the surface of the NCBM12@M sample is illuminated, the temperature increases; however, heat transfer to the bottom layer has not yet reached equilibrium. Heat transfer from the NCBM12@M sample to the surrounding environment also contributes to this discrepancy. The calculated photothermal conversion efficiency of the NCBM12@M sample is 89.26%. The solar-to-thermal energy conversion and storage efficiency, h, can be determined by calculating the ratio of the thermal energy stored in the material to the incident light radiation energy received during the phase transition, as shown in the following formula:
[0121]
[0122] Where m represents the mass of the PW composite material, H m represents the melting enthalpy of PCM, P refers to the irradiation intensity of the solar simulator, S represents the irradiated surface area of PCM, and t1 and t2 represent the phase change time of PCM under solar driving before and after phase change, respectively.
[0123] In summary, the addition of MWCNTs and BNNS significantly improved the photothermal conversion and thermal storage performance of CPCM. This enhancement can be attributed to the fact that MWCNTs act as efficient light absorbers and molecular heaters, effectively converting solar energy into thermal energy and promoting the thermal storage process of CPCM.
[0124] In summary, the thermal conductive storage material provided by the present invention effectively avoids the agglomeration of MPCM by fixing MPCM on the surface of CNF; the triple support effect of microencapsulation and the continuous network of NR and CNF is expected to give the thermal conductive storage material significant leakage resistance. NR serves as a flexible matrix. After curing, the NR cross-linked skeleton gives the MPCM room temperature flexibility, allowing the CPCM based on MPCM to bend or twist without breaking. In addition, BNNS and MWCNT as binary synergistically reinforced thermal conductive fillers are self-assembled and dispersed on the CNF cross-linked network to form an efficient thermal conductive path, providing technical support for the thermal conductivity of the synergistically reinforced material; at the same time, the CNF / BNNS / MWCNT thermal conductive path based on the CNF cross-linked network is introduced into the polymer matrix, which effectively improves the thermal conductivity of the polymer-based flexible thermal conductive storage material. The resulting thermal conductive storage material with flexibility, leakage prevention and enhanced thermal conductivity can be used to achieve effective thermal management of batteries, greatly expanding its application scenarios.
[0125] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.
Claims
1. A method for preparing a thermal conductive heat storage material based on a CNF / NR double cross-linked network, characterized in that: The steps include: 1) dispersing a certain amount of thermal conductive filler into the CNF water suspension and homogenizing it to obtain a first mixed solution; 2) uniformly mixing the first mixed solution prepared in step 1) with the phase change capsules to obtain a second mixed solution; 3) dropping natural rubber latex into the second mixed solution prepared in step 2), stirring evenly to obtain a third mixed solution; 4) The third mixed solution prepared in step 3) is frozen, dried and pressed to obtain a heat-conducting heat storage material.
2. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 1, characterized in that: The thermal conductive material includes BNNS and MWCNT, and the mass ratio of BNNS to MWCNT is (3-8): (2-5).
3. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 1, characterized in that: The process parameters of the homogenization treatment in step 1) are homogenization at 4000-8000 rpm for 5-15 minutes at room temperature.
4. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 1, characterized in that: The freezing condition in step 4) is freezing at -25 to -15°C for 6 to 18 hours; the drying condition is freeze drying at a pressure of less than 20Pa and a temperature of -60 to -50°C for 40 to 50 hours; the pressing condition is pressing at room temperature and 1 to 3MPa for 3 to 8 minutes.
5. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 4, characterized in that: The mass percentage of the thermally conductive filler in the thermally conductive heat storage material is 4-12%.
6. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 4, characterized in that: The natural rubber latex is NR natural rubber latex, the phase change capsule is phase change paraffin microcapsule, and the mass fraction of the CNF water suspension is 1-3%.
7. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 4, characterized in that: The mass ratio of the phase change capsule to CNF is (5-15):
1.
8. The method for preparing a heat-conducting and heat-storage material based on a CNF / NR double cross-linked network according to claim 4, characterized in that: The mass ratio of the phase change capsule to NR is (4-8):(2-5).
9. A thermal conductive heat storage material prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the heat-conducting and heat-storage material according to claim 9 in photothermal materials and wearable materials.
Citation Information
Patent Citations
{0><}0{>Preparation method of high-strength natural rubber (NR) / carbon nano tube (CNT) conductive composite film
CN105949536A
Heat conduction and storage film and preparation method thereof
CN114425898A